2019
DOI: 10.1038/s41398-019-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating proteomic, sociodemographic and clinical data to predict future depression diagnosis in subthreshold symptomatic individuals

Abstract: Individuals with subthreshold depression have an increased risk of developing major depressive disorder (MDD). The aim of this study was to develop a prediction model to predict the probability of MDD onset in subthreshold individuals, based on their proteomic, sociodemographic and clinical data. To this end, we analysed 198 features (146 peptides representing 77 serum proteins (measured using MRM-MS), 22 sociodemographic factors and 30 clinical features) in 86 first-episode MDD patients (training set patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Across our models, the most predictive symptom of MDD was leaden paralysis, which refers to an extreme form of fatigue or heavy, leaden feelings in the arms and legs. This finding is in line with a recent study by Han et al [ 61 ], whose findings revealed that leaden paralysis was a robust and important predictor of first-onset MDD. Critically, although leaden paralysis is included in the DSM-5 specifier for atypical depression, it is not deemed a core feature of the disorder [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Across our models, the most predictive symptom of MDD was leaden paralysis, which refers to an extreme form of fatigue or heavy, leaden feelings in the arms and legs. This finding is in line with a recent study by Han et al [ 61 ], whose findings revealed that leaden paralysis was a robust and important predictor of first-onset MDD. Critically, although leaden paralysis is included in the DSM-5 specifier for atypical depression, it is not deemed a core feature of the disorder [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…13−15 Although these studies proposed many candidates, such as C3, C4BPA, CFI, B2RAN2, ENG, RAB7A, ROCK2, XPO7, PDGF-BB, and TSP-1, their clinical relevance and significance remain unknown, necessitating further validation of these biomarkers. 13−16 Moreover, although MS-based targeted proteomic techniques have been used in studies to differentiate mood disorders from HCs or between HCs and severity of a specific mood disorder, 19,20 no study has attempted to discriminate MDD from BD using MSbased quantitative targeted proteomic methods, such as multiple reaction monitoring (MRM)-MS, at least to our knowledge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The returned DBS samples were analysed for neuropsychiatric biomarker levels using a validated targeted proteomic approach [27][28][29] . The method targeted 203 unique peptides representing 120 proteins (Supplementary Table 1) selected based on their association with psychiatric conditions and concentration in the blood 28 .…”
Section: Methodsmentioning
confidence: 99%